Sr-85 Profile Counting and Scanning in Early Diagnosis of Bone Metastases - Taskinen, Penti J.; Vähätalo, Soini (Nuklearmedizin - NuclearMedicine, 1971)
Most of the 105 patients examined in 1966—1968 were suspected of having bone metastases caused by a malignant tumour. They were studied by 85S scanning and profile counting. The results obtained by the two methods were similar and complementary. A new method is presented for the drawing of a normal curve in profile counting in which the sources of error are reduced to a minimum through comparison with both the value for the heels and the values of vertabrae Th VII and LIV.